Capital budgeting system and management in Petronas Melaka Refinery / Rahmat Md Jali - Md Jali, Rahmat (2009)
This study provides an analysis regarding to Capital Budgeting System and Management. The purpose of this study is to analyze the flow of capital budgeting system, information features, the appropriate method to estimate the budget and general about capital budgeting system in Petronas Refinery Melaka. This study is to identify which components or elements in capital budgeting system. In Petronas Management System, System application and programme (SAP) which is fully manages include General Ledger, Accounts Payable/Receivable, Project and Fixed Assets, Treasury and Tax section and many more. Capital Budgeting is under Project and Fixed Asset Section and (SAP ) manages the projects, material, inventory, assets and from that we can create a capital budgeting after all the items was classified into the classes or groups. These studies also try to answer the issues that arise in management finance and accounting section under Petronas Refinery Melaka (PPMSB). In order to analyze the issues, the data collected from primary and secondary sources. Data and information had been collected form the article, internet, journals and annual report and as well as from interviewing both of executives which are Project Accounting unit and Fixed Asset unit and other staffs are briefly explain on the research finding.